PENERAPAN KEGIATAN LITERASI DALAM PEMBELAJARAN SOSIOLOGI DI KELAS X IPS 1 SMA ISLAMIYAH PONTIANAK - Selyasari, Selyasari; Sulistyarini, Sulistyarini; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this reseach is â€œthe application of literacy activities in learning sociology in class X IPS1 Pontianak Islamic High Schoolâ€. This study aims to determine the process of implementing pre-reading activities, reading activities, and post-reading activities in learning sociology in class X IPS1 Pontianak Islamic High School. This study uses qualitative research methods in descriptive form. Data collection tools use observation guides, interview guides, and documentation. This study used four student informants and one sociology subject teacher. The results of this study indicate the implementation of literacy activities in learning sociology in class X IPS1 Pontianak Islamic High School has been applied, that the teacher conducts prabaca activities, teacher and students do reading activities in the teaching and learning process, and the teacher instructs student to do post-reading activities such as making resumes and conclusions, then displayed in from of the class. However, the application of literacy is not optimal due to insufficient time and class X IPS1 does not have LKS books but only photocopies are copied according to the material that has been delivered.Â Keyword: Literasi Activities, Sosiology learning